A Comprehensive Review of Analytical Approaches for Carotenoids Assessment in Plant-Based Foods: Advances, Applications, and Future Directions - Marcin A. Kurek; Havva Aktaş; Patryk Pokorski; Ewelina Pogorzelska-Nowicka; Jorge A. Custodio-Mendoza (Applied Sciences)
Carotenoids are essential bioactive compounds in plant-based foods, valued for their antioxidant properties and role in human health. Accurate quantification of these pigments is critical for food science, nutrition, and health research, yet their analysis remains challenging due to structural complexity, susceptibility to degradation, and matrix interferences. This review comprehensively evaluates analytical techniques for carotenoid assessment, focusing on chromatographic advancements, emerging detection strategies, and sustainability considerations. High-performance liquid chromatography remains the gold standard due to its precision, while novel approaches such as supercritical fluid chromatography and core–shell particle technology enhance efficiency and environmental sustainability. Machine learning and lab-on-a-chip technologies are also emerging as promising tools for rapid, cost-effective, and miniaturized analysis. Challenges in standardization, regulatory gaps, and the limited availability of certified reference materials persist, emphasizing the need for fully validated analytical methodologies. Future research should prioritize green analytical techniques and interdisciplinary strategies to improve sensitivity, reproducibility, and environmental impact. This review provides a critical resource for researchers and industry professionals willing to refine carotenoid analysis for food science, nutrition, and biotechnology applications.